Curriculum Design for High School of Theology & Christian High School Based on Indonesian National Qualifications Framework (KKNI) - Oci, Markus; Suparti, Hana; Wahyuni, Sri; Soeharto, Daniel (International Journal of Educational Narratives, 2024)
Background. Higher education is a formal institution in government educational institutions. Higher education is expected to be a tool that assists everyone in obtaining adequate resources. As a result, understanding the system in a tertiary institution is critical in order to support the education system. Purpose. The objective of this research was to help tertiary institutions understand their role in developing superior human resources by developing an IQF-based curriculum system that produces graduates that meet the needs of the community. \Method. The descriptive qualitative method was used, along with a literature review. Results. The author explained each of the findings using a literature review. According to the findings of this study, tertiary institutions’ High School of Theology & Christian High School must determine graduate profiles, graduate learning outcomes, study materials, course formation, course grouping, course structure provisions, and semester lesson plans in the lecture curriculum. Conclusion. Each tertiary institution must pay attention to new systems in order to create superior human resources in their fields in order to advance the curriculum.